Social Learning and Community Empowerment in Halal Certification: A Qualitative Study of P3H Mentoring at LP3H IAIN Bone - Nurkhadijah N; Lukman Arake; Kamiruddin Kamiruddin (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study analyzes social learning processes and community empowerment, framing P3H mentoring as a form of social intervention that drives changes in MSMEs' knowledge, attitudes, and behavior, through the transformation of halal certification awareness among Micro, Small, and Medium Enterprises (MSMEs) through Halal Product Process Assistance (P3H) conducted by the Halal Product Process Assistance Institution (LP3H) of  IAIN Bone in Bone Regency, departing from the issue that increased access to halal certification programs has not always been followed by changes in MSME understanding and awareness regarding the substance of halal product assurance. Methodology: This study employs a descriptive-analytical qualitative approach with data collection through observation, in-depth interviews, and documentation, selecting informants via purposive sampling consisting of LP3H management, P3H assistants, and MSME actors, and analyzing data through reduction, coding, data display, and conclusion verification, with data validity tested through triangulation and member checking. Main Findings: The P3H assistance takes place through four stages: preparation, pre-certification, data input and field verification, and post-certification, driving a shift in MSME awareness across cognitive, affective, and conative aspects from viewing halal certification as an administrative obligation toward seeing it as an instrument for consumer protection and business development, supported by the SEHATI program, proactive assistance approaches, and religious-economic motivations, while hindered by low digital and legal literacy, data security concerns, and SIHALAL system constraints. Novelty/Originality of this study: This study offers a distinct novelty by examining the transformation of awareness in resolving the specific phenomenon of 'cultural halal', the deep-rooted community belief that food produced by fellow Muslims inherently guarantees halal status without formal certification through structured P3H mentoring, highlighting that certification effectiveness depends on bridging traditional assumptions with formal legal compliance across cognitive, affective, and conative dimensions.